Civiliza tion and barbarism. The establishment of a ‘colonial difference’ during the debates of the sixteenth century, and its cover up as ‘cultural difference’ (Andamios, Revista de Investigación Social, 2012)
This paper analyzes the concepts of ‘civilization’ and ‘barbarism’ underlying ‘Valladolid debate’ in the sixteenth century, in the light of critical thinking in Latin America (modernity / coloniality). Reviewing and summarizing of the literature, demonstrate that the arguments of Bartolome de Las Casas, and those who openly defended the dignity of the natives, were a ‘cover up’ of the ‘colonial difference’ as a ‘cultural difference’. This ‘cover up’, not only serve as a strategy or mechanism of justification and legitimation of the ‘conquest’, and its consequent domination and exploitation of the indigenous, but also as a platform on which to record the idea of ‘civilizing the other’ (or idea of ‘progress’) during the Enlightenment of the seventeenth and eighteenth centuries.
Keywords: Civilization and barbarism; colonial difference; cultural difference; Bartolomé de Las Casas; modernity/coloniality